PRODUCTION SYSTEM OF PUFFER FISH (Lagocephalus spadiceus) PRODUCT AT JAYA UTAMA AGROINDUSTRIAL - Nuril Muyassaroh; Triana Dewi Hapsari (UNEJ e-Proceeding, 2018)
Puffer fish until now has not been explored optimally because it is known as a toxic commodity and difficult to process. Jaya Utama Agroindustrial is an agro-industry that processes Puffer fish into various preparations, namely fillets, rambak, and Puffer fish bone peanut brittle. L.spadiceus that is used by Agroindustri Jaya Utama has poison in the part of his heart. Based on this, the purpose of this research is to find out the production system from the production process, the type of production, and the layout of production facilities of Agroindustri Jaya Utama. The sample determination method uses purposive sampling. Data collection method uses observation, interview, documentation and literature study techniques. The analytical method is descriptive. The result of this research is the production system from the production process, the type of production, and the layout of production facilities used by agro-industries. The analytical method used is descriptive. The result showed that the production process of Puffer fish fillets focused on the process of weeding, the production process of rambak focused on the separation of the skin and the bone crest of Puffer fish focusing on the drying stage; The type of production applied by agro-industry is the intermittent type; The layout of production facilities used is layout by process.